Exploring EFL Secondary Students Practice Peer Feedback in Speaking Anxiety Classrooms - Addin, Desyifa Medita; Pahlevi, Muhammad Reza; Srisudarso, Mansyur (Peneliti.net, 2023)
Learning English in EFL classes is still challenging. One of the difficulties experienced was in speaking practice class. Several factors affect students' difficulties in speaking in class, one of which is the anxiety factor. Several studies have shown peer feedback to help students reduce anxiety in speaking classes. This study explores the practice of implementing peer feedback on students' anxiety in speaking classes. The research was conducted at SMP Negeri 3 Klari using a qualitative approach and narrative inquiry method. The research was conducted using instructional procedures. Observations and interviews were used to collect data, which were then analyzed using thematic analysis. Research shows that there were still many students who show symptoms of anxiety in speaking classes which are shown by several different symptoms, one of which is nervousness. Peer feedback was carried out by identifying the problems, explaining, and giving suggestions. In practice, peer feedback shows that peer feedback activities are a helpful first experience and interesting. In addition, peer feedback can help reduce EFL students' anxiety in speaking classes because activities are carried out in groups.